2010
DOI: 10.1161/strokeaha.109.574244
|View full text |Cite
|
Sign up to set email alerts
|

Size Ratio Correlates With Intracranial Aneurysm Rupture Status

Abstract: Background and Purpose-The prediction of intracranial aneurysm (IA) rupture risk has generated significant controversy. The findings of the International Study of Unruptured Intracranial Aneurysms (ISUIA) that small anterior circulation aneurysms (Ͻ7 mm) have a 0% risk of subarachnoid hemorrhage in 5 years is difficult to reconcile with other studies that reported a significant portion of ruptured IAs are small. These discrepancies have led to the search for better aneurysm parameters to predict rupture. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(137 citation statements)
references
References 21 publications
3
130
0
4
Order By: Relevance
“…The size ratio (SR) value of the ruptured aneurysms is significantly larger than unruptured aneurysms. This result is based on the ratio of aneurysms and aneurysmal arteries by Rahman (16). The increased bottleneck factor and the height-width ratio are considered inherent characteristics of the ruptured aneurysms in the control of ruptured and unruptured aneurysms by Hoh (8).…”
Section: Discussionmentioning
confidence: 99%
“…The size ratio (SR) value of the ruptured aneurysms is significantly larger than unruptured aneurysms. This result is based on the ratio of aneurysms and aneurysmal arteries by Rahman (16). The increased bottleneck factor and the height-width ratio are considered inherent characteristics of the ruptured aneurysms in the control of ruptured and unruptured aneurysms by Hoh (8).…”
Section: Discussionmentioning
confidence: 99%
“…The SR factor is introduced representing the ratio of the caliber of the carrier vessel and the size of the aneurysm as a predisposing factor for aneurysm rupture (8,17,26,31).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers such as Weir et al [2] and Nader-Sepahi et al [3] concurred with the correlation between AR and rupture probability. On the other hand, Dhar et al [4], Tremmel et al [5] and Rahman et al [6] reported a high correlation of SR with rupture status. Tremmel et al suggested aneurysms with SRs larger than 2.0 could have a potential risk of rupture.…”
Section: Significance Of Ar and Srmentioning
confidence: 97%
“…Aspect ratio (AR) [1][2][3] and size ratio (SR) [4][5][6] were reported to have significant correlations with probability of aneurysmal rupture, being recognised as promising reference parameters for rupture prediction. AR is a ratio of aneurysmal dome depth to neck width while SR is defined as a ratio of dome length to parent artery diameter.…”
Section: Introductionmentioning
confidence: 99%